Non Alcoholic Fatty Liver Disease (NAFLD) and Type 2 Diabetes Mellitus - Pradhan, Bickram; Peeyush, Denis (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: The pandemic of obesity and type2-diabetes mellitus has led to a increasing prevalence of Non Alcoholic Fatty Liver Disease (NAFLD) globally, including developing countries. The current epidemic of NAFLD is reshaping the field of hepatology because patients with NAFLD creased risk for not only liver-related morbidity and mortality but also cardiovascular disease. NAFLD also increases the risk of developing diabetes. Hence patients with diabetes need to be screened for the presence of NAFLD and vice-versa. It is of paramount importance to differentiate between simple steatosis from Non Alcoholic Steatohepatitis (NASH), the later being more associated with hepatic as well as extra hepatic complications.